Social Campaign Media Design of Books for Papua - Oktavian Eka Wahyuning Tyas; Didit Widiatmoko Soewardikoen (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2015)
Education facilities in Papua is insufficient, so the amount of illeteracy is still high in that region. Later, there is a community that named as